Brain function assessment of acupuncture for chronic insomnia disorder with mild cognitive dysfunction based on fNIRS: protocol for a randomized controlled trial - Wang, Tianyu; Li, Zhi; Ma, Tingting; Zhu, Fengya; Yang, Bin; Kim, Sieun; Miao, Runqing; Wu, Jie (Frontiers in Neurology, 2024)
BackgroundChronic Insomnia Disorder (CID) is highly prevalent among older adults and impairs cognitive function. Insomnia accelerates the progression of mild cognitive impairment (MCI) and increases the risk of developing dementia. Acupuncture has been demonstrated in improving sleep quality and cognitive function. This study aims to explore the functional brain characteristics of CID with MCI patients and to assess the effects of acupuncture therapy using functional near-infrared spectroscopy (fNIRS).Methods and designThis study is a single-center randomized controlled trial. Participants will be randomly assigned to the manual acupuncture group or the placebo acupuncture group for an 8-week intervention period. fNIRS data will be collected during resting test and working memory test at baseline and at end of the intervention. The primary outcome is the change of the Montreal Cognitive Assessment (MoCA) score, secondary outcomes include the change of Mini-Mental State Examination (MMSE), Insomnia Severity Index (ISI), Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder Scale (GAD-7), and Apathy Evaluation Scale-Informant (AES-I).DiscussionThe results of the study will provide insights into the effects of acupuncture on sleep quality and cognitive performance in CID with MCI patients. By utilizing fNIRS technology, we will elucidate the neural functional characteristic underlying the therapeutic benefits of acupuncture.Clinical trial registrationhttps://ClinicalTrials.gov, identifier ChiCTR2300076182.